STRUCTURAL ASPECT OF INNOVATION ACTIVITY - Dadajonova Martabakhan Mahmudovna (Journals Park Publishing, 2024)
This article describes the main stages of innovative activity, its life cycles and parties involved in innovative processes
Keywords: Life cycle, organizational and economic mechanism, innovative economy, innovative index.